Legal Protection for a Substitute Notary on the Deed Done Before Him - Isyara Hadza Maulina; Siti Hamidah; Titik Soeryati Soekasi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Substitute Notary has the same authority and responsibility as the Notary being replaced. And the responsibility of the Substitute Notary remains attached even though his position has ended. Even though they have responsibilities like a notary, there are differences in terms of legal protection between Notary and Substitute Notary. This type of research is normative legal research with a state approach and a case approach. The results of this study indicate that the provisions in Article 66 Notary Position Act only provide legal protection for Notaries but do not include Substitute Notaries. Legal Protection for Substitute Notaries can be done through preventive legal protection carried out by the Substitute Notary Public himself by carrying out his/her position carefully, thoroughly and based on the Notary Position Act, code of ethics and other statutory regulations. In addition, legal protection for Substitute Notaries related to summons for the benefit of the judiciary still follows general provisions, namely through the obligation to deny and the right to deny.